Level of uncertainty of caregivers towards the patient hospitalized pediatric (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
The hospitalisation of paediatric patients entails various psychological implications for their caregivers. The main objective of this study was to determine the degree of uncertainty experienced by caregivers of hospitalised children using the Parents test at the Instituto Ecuatoriano de Seguridad Social in Riobamba during the years 2021-2022. The research adopted a descriptive, prospective and cross-sectional approach, collecting data through the Parents test in relation to different variables. This test was applied to caregivers of paediatric patients hospitalised in the paediatric service of the IESS General Hospital. The results revealed that of the 110 surveys conducted, 0.9% of the respondents showed a low score (less than 55 points), 14.5% obtained a moderate score (between 56 and 85 points), and 84.5% obtained a high score (more than 85 points). It is concluded that there is a significant level of uncertainty among caregivers of hospitalised children, with 84.5% experiencing a high degree of uncertainty, followed by 14.5% with moderate uncertainty, and only 0.9% with a low level of uncertainty.